PENETAPAN KADAR AIR SIMPLISIA DAUN KEMANGI (Ocimum basilicum L.) BERDASARKAN PERBEDAAN METODE PENGERINGAN - Wijaya, Andi; Noviana, Noviana (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2022)
Drying is one of the steps in making basil leaves simplicia. Drying is done to reduce the water content of simplicia. This study aims to determine the effect of the drying method on the water content of simplicia basil leaves. This research is an experimental post-test only group design. The basil leaves were dried using 2 methods, namely the direct sunlight method with a black cloth cover and the oven method at 50°C for 7 hours. The dried simplicia was then determined the water content using the gravimetric method. The water content data were analyzed using the Shapiro-Wilk test to determine the normality of the data, followed by the Independent T-test with a 95% confidence level. The results showed that the average moisture content of the drying method using the oven was 9,58±0.15% and the drying method using sunlight was 11,39±0.15%. These results indicate a significant difference (p≤0,05). This study concludes that different drying methods can affect the water content of basil leaves simplicia